HUBUNGAN TINGKAT PENGETAHUAN DAN MOTIVASI IBU DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS I DENPASAR BARAT - Ni Putu Ayu Dinda Paramitha; Desak Putu Sukraniti; I G A Ari Widarti (Poltekkes Kemenkes Denpasar dan DPD PERSAGI Bali, 2022)
Nutrition problems occur in every life cycle, starting in the womb (fetus), infants, children, adults and old age. To get good nutrition in infants, the mother must as soon as possible breastfeed her newborn baby because breast milk provides complete and sufficient nutrition in maintaining health and maintaining the survival of the baby. After the mother is 9 months pregnant, the baby will get the main food from exclusive breastfeeding. The government has issued Government Regulation No. 33/2012 concerning exclusive breastfeeding. Based on the Profile of the Denpasar City Health Office (2017) in 2017 exclusive breastfeeding coverage in Denpasar was 47.65%, while the lowest exclusive breastfeeding coverage was in Pusksesmas I West Denpasar which was 41.27%. The low coverage of Exclusive ASI is closely related to knowledge and motivation of mothers about Exclusive ASI. The purpose of this study was to determine the relationship between the level of knowledge and motivation of mothers with exclusive breastfeeding in the working area of the West Denpasar Health Center I. This type of research is observational with cross-sectional design and the number of research samples is 71 women under two. Data collected by interview method. Data analysis used the Yates Chi Square Correction statistical test. The results showed that, mothers who had a good level of knowledge were 94.4%, sufficient level of knowledge (5.6%), and the level of knowledge was lacking. While the motivation of mothers (73.2%) included good categories, as many as (26.8%) included enough categories, and there were no mothers with poor motivation. It is known that (45.1%) mothers give exclusive breastfeeding, and (54.9%) mothers do not give exclusive breastfeeding. Chi square test shows there is no relationship between the level of knowledge and motivation of mothers in the working area of the West Denpasar Health Center I, p value = 0.617. There is a relationship between mother's motivation towards exclusive breastfeeding in the working area of the West Denpasar Health Center I, p value = 0.001.Keywords: Knowledge Level, Mother's Motivation, Exclusive Breastfeeding